Poly(vinylidene fluoride)-based nanocomposite employing oriented Bi2S3 nanorods with double-shell structure for high dielectric performance and loss suppression. (8th February 2019) - Zhang, Lingyu; Wang, Yao; He, Dalong; Deng, Yuan
Abstract: For polymer-based nanocomposites, designing the nanostructures of fillers, their distribution inside matrix as well as interfaces with the polymer is of crucial importance to achieve high dielectric performances. One-dimensional semiconductor Bi2 S3 nanorods coated with homogeneous SiO2 and polydopamine (PDA) double shell layers were imported into the poly(vinylidene fluoride) (PVDF) with parallel arrangement via uniaxial stretching to form Bi2 S3 @SiO2 @PDA/PVDF nanocomposite. The dielectric performances of oriented Bi2 S3 @SiO2 @PDA/PVDF were studied in comparison with its counterparts employing Bi2 S3 fillers without shell layers or alignment. A microcapacitor model was used to accurately estimate the dielectric constant along perpendicular direction. Coating conductive Bi2 S3 nanorods with insulating SiO2 @PDA double layer remarkably reduces the dielectric loss of the nanocomposite, while alignment of one-dimensional Bi2 S3 @SiO2 @PDA nanorods endows electrical properties anisotropy, which was understood from J-V curves measured along two directions and moreover, via three-dimensional finite element analysis, unambiguously revealing the effects of aligned core-shell structured fillers on local electric field and current density distribution. This study provides a promising and facile approach for designing high performance dielectrics. Graphical abstract: